1996
DOI: 10.1093/nar/24.7.1308
|View full text |Cite
|
Sign up to set email alerts
|

Differential Discrimination of DNA Polymerases for Variants of the Non-Standard Nucleobase Pair Between Xanthosine and 2,4-Diaminopyrimidine, Two Components of an Expanded Genetic Alphabet

Abstract: Mammalian DNA polymerases alpha and epsilon, the Klenow fragment of Escherichia coli DNA polymerase I and HIV-1 reverse transcriptase (RT) were examined for their ability to incorporate components of an expanded genetic alphabet in different forms. Experiments were performed with templates containing 2'-deoxyxanthosine (dX) or 2'-deoxy-7-deazaxanthosine (c7dX), both able to adopt a hydrogen bonding acceptor-donor-acceptor pattern on a purine nucleus (puADA). Thus these heterocycles are able to form a non-stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
65
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 29 publications
2
65
0
Order By: Relevance
“…Experiments in which EDC or MgCl 2 was omitted were used as controls. A standard ligation experiment with unmodified oligonucleotides GL 5 and Im(p*L 3 p) aligned on the unmodified template Tem was carried out under identical conditions to permit comparison between a standard ligation reaction and ligation to a covalent base pair. A ligation reaction between TemAF and p*L 5 (Fig.…”
Section: Overview Of the Synthesis Of A Nucleic Acid Incorporating A mentioning
confidence: 99%
See 3 more Smart Citations
“…Experiments in which EDC or MgCl 2 was omitted were used as controls. A standard ligation experiment with unmodified oligonucleotides GL 5 and Im(p*L 3 p) aligned on the unmodified template Tem was carried out under identical conditions to permit comparison between a standard ligation reaction and ligation to a covalent base pair. A ligation reaction between TemAF and p*L 5 (Fig.…”
Section: Overview Of the Synthesis Of A Nucleic Acid Incorporating A mentioning
confidence: 99%
“…In Fig. 5, lane 9, we show the product p*TemAL 5 p*F from a ligation reaction between 5Ј-32 P-labeled TemAF and activated 5Ј-32 P-labeled L 5 and, in Fig. 5, lane 10, the product from the corresponding reaction with the reduced Fig.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…It has been reported that 2'-deoxyxanthosine (1) might expand the genetic code when it pairs with a pyrimidine-2,4-diamine C-nucleoside [14]. However, experimental data show that the enzymatic incorporation of a pyrimidine-2,4-diamine C-nucleoside triphosphate on a DNA template containing compounds 1 or 3 is slow compared to the canonical nucleotides [14].…”
mentioning
confidence: 99%